Proceso atención de enfermería en paciente adulto mayor con enfermedad pulmonar obstructiva crónica. - Valencia Castillo, Angela Katherine (2022)
Chronic obstructive pulmonary disease (COPD) is a prevalent disease, associated with factors such as smoking, exposure to external smoke, among others; it is important to determine its epidemiology, to analyze the effects of environmental and physiological factors of chronic obstructive pulmonary disease, very common in our environment, emphysema and chronic bronchitis are the two most frequent conditions that contribute to the development of COPD, it is a disease life-threatening persistent lung disease that can cause shortness of breath (initially associated with exertion) and factors that tend to exacerbate. Through the nursing approach, the case of an 87-year-old female patient with a history of arterial hypertension, diagnosed with COPD, who during her youth was a chronic smoker and who throughout her life has used traditional kitchens (use of firewood) for the preparation of food at home, presenting complications for refusing to receive medical treatment. COPD in Ecuador is presented as an underestimated disease and of low detection in the first level of attention, the present work was selected to give visibility to the approach of these patients and it is constituted in improving the lifestyle, applying our knowledge acquired in detection and timely management of the same to reduce future complications.